Traducir derechos, traducir culturas - Villanueva Jordán, Iván (2023)
Iván Villanueva (Perú) - Moderador; Luis Andrade Ciudad (Perú) - Autor; Rosaleen Howard (Irlanda) - Autora; Raquel de Pedro Picoy (España) - Autora